AB0491 The association of baseline hyperuricemia in premenopausal women with systemic lupus erythematosus and development of nephritis. (15th June 2017) - Lim, DH; Hong, S; Oh, JS; Kim, Y-G; Lee, C-K; Choi, SW; Yoo, B
Abstract : Background: Renal involvement is a common and serious manifestation of SLE. Hyperuricemia may be associated with lupus nephritis as a result of renal damage. However, it is not yet well known whether hyperuricemia is independently associated with renal involvement even in patients without known predisposing factors for hyperuricemia such as decreased renal function, old age, male gender, menopause, and drugs. Objectives: The aim of this study was to evaluate the association of baseline serum uric acid level and development of nephritis in patients diagnosed with SLE. Methods: We retrospectively reviewed electronic medical records of 101 female SLE patients whose ages at the time of diagnosis (baseline) were 45 years old or below in a tertiary medical center from January 2000 to March 2015. SLE with renal involvement was diagnosed when patients met the renal disorder of the 1997 ACR criteria for SLE. We compared baseline serum uric acid levels of the SLE patients who had nephritis at the time of diagnosis or later (nephritis group) with the patients who had not developed nephritis (non-nephritis group) during follow-up period. Results: Among 101 patients, 22 (22%) had hyperuricemia (serum uric acid ≥6 mg/dL) at baseline and 45 (45%) had developed nephritis during follow-up period (median 6.1 years). There were significant differences in baseline serum uric acid level, glomerular filtration rate (GFR), anti-dsDNA antibody and complement level between non-nephritis group and nephritis group (Table). Interestingly, among 59 patients with normal renal function (baseline GFR ≥90 mL/min/1.73m 2 ), baseline serum uric acid level was also significantly higher in the nephritis group than non-nephritis group (Table). Moreover, the patients with hyperuricemia at baseline were more likely to develop nephritis than those without hyperuricemia during follow-up period (64% vs. 39%, p =0.042) (Figure). Conclusions: These findings suggest that high serum uric acid level at the time of diagnosis in premenopausal women with SLE may be independently associated with nephritis. More careful evaluation would be required for development of nephritis in such patients. Disclosure of Interest: None declared